Infrastructure Project Governance: An Analysis Of Public Sector Project In Northern Pakistan - Khan, Asadullah; Hussain, Ammar; M., Waris; Ishak, Ismail; Ilyas, Muhammad (Penerbit Universiti Malaysia Pahang, 2018)
Infrastructure projects in developing countries have been criticized for cost overrun, delay, substandard construction works, ineffectiveness and low efficiency. In this regard, the project governance approach offers a structured mechanism to analyze and address all of these inherent risks in a timely manner. This study has reviewed the academic literature relating to the need for project governance on infrastructure projects in order to assess the potential causes of the success and failure of projects. The review is further elaborated by discussing a case study, which represents an example of the ill planning of infrastructural development projects in the Northern region of Pakistan. This study suggests the need for exploring potential applications of project governance practices in public sectors of developing countries.